If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(t + -2) = t + 10 Reorder the terms: 5(-2 + t) = t + 10 (-2 * 5 + t * 5) = t + 10 (-10 + 5t) = t + 10 Reorder the terms: -10 + 5t = 10 + t Solving -10 + 5t = 10 + t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-1t' to each side of the equation. -10 + 5t + -1t = 10 + t + -1t Combine like terms: 5t + -1t = 4t -10 + 4t = 10 + t + -1t Combine like terms: t + -1t = 0 -10 + 4t = 10 + 0 -10 + 4t = 10 Add '10' to each side of the equation. -10 + 10 + 4t = 10 + 10 Combine like terms: -10 + 10 = 0 0 + 4t = 10 + 10 4t = 10 + 10 Combine like terms: 10 + 10 = 20 4t = 20 Divide each side by '4'. t = 5 Simplifying t = 5
| 9p+6=3(p+8) | | 4b=6b+-19 | | 4(x+2)=3x+11 | | 3x^2+10+8=0 | | 3p^2-28=27p | | 4(n-1)=n+14 | | 4y^3-3=-12y^2+y | | 10+2z=20 | | -6+x=-10 | | 12t-1=14t-5 | | 8k+10=13k-5 | | 3v^2-7v-20= | | 3a=5a-18 | | 6(x+2)=3(x-5) | | 5x+37=14x-62 | | x^2+5x+18=9 | | 4x+7=x+16 | | 15r+22=97 | | 3(x-4)+5(x+3)=2(3x-5)-6 | | 6(2x-5)=42 | | -4x+2(4-3x)=8-10x | | 9x-21=3+3 | | 3r+12=r+34 | | 4p+8=10p+2 | | -x^2+50x-350=0 | | 8t^2-6t=9 | | x^5-x^4+9x^3-9x^2=0 | | 2x+3=24 | | 5x^2+36x+36=0 | | 6(x-8)-(2x-2)=5x-1 | | .5(20z+18)-8=9(z-3) | | 7x+19y=-3 |